Pengaruh Model Pembelajaran Somatic, Auditory, Visual, Intellectual (SAVI) terhadap Kemampuan Representasi Matematis Siswa di Madrasah Ibtidaiyah - Jailani, M. Syahran; Siagian, Fitri Nauli; Annissa (IBTIDA', 2024)
This inquire about was based on the preparatory perception almost the moo numerical representation capacities of understudies at the Nurul Yaqin Private Madrasah Ibtidaiyah. This inquire about pointed at finding out whether there was impact of SAVI learning demonstrate on students' numerical representation capacities. It was test investigate with Semi Eksperimental Nonequivalent Control Gather Desain. The fourth-grade understudies at Nurul Yaqin Private Madrasah Ibtidaiyah were the populace of this inquire about. Examining add up to method was utilized in this investigate, the fourth-grade understudies of course A were as the control gather and the understudies of course B were as the test gather. Test, survey, perception, meet, and documentation were the procedures of collecting information with the rebellious of collecting information within the frame of SAVI learning show test questions, scientific representation capacity surveys, perception sheet, and documentation photo. The information investigation utilized by analysts is utilizing information typicality tests, information homogeneity and theory testing. The comes about of the investigate conducted appeared that the numerical representation capacities instructed utilizing the Substantial, Sound-related Visual, Intellectualy (SAVI) learning show were higher than those of understudies instructed utilizing the address strategy. The results of hypothesis testing with the Independent Simple t-Test are the sig value. (2-tailed) of 0.045 < 0.05, it can be concluded that the SAVI learning show variable (X) includes a contribution to numerical representation capacity (Y). Based on testing the speculation it can be concluded that learning with the Substantial, Sound-related Visual, Mental (SAVI) has an impact students' scientific representation capacities at the Nurul Yaqin Private Madrasah Ibtidaiyah .